PENGARUH INFLASI, KEBIJAKAN DEVIDEN, LEVERAGE, NILAI TUKAR RUPIAH, DAN TINGKAT SUKU BUNGA TERHADAP NILAI PERUSAHAAN (Studi Empiris Perusahaan yang Terdaftar Di LQ45 2012-2014) - Muhammad Taufan, 14.05.62.0025 (Students Journal of Accounting and Banking, 2016)
This research is a research that investigates the effects of inflation, dividend policy, leverage, rupiah exchange rate, and interest rate toward the company value in the company registered in LQ45 index.The method of collecting data in this research is purposive sampling with research period in 2012 to 2014. The correlations and effects among variables are explained by using double regression analysis method. The results of research show that the effects of inflation, dividend policy, leverage and are negative significant, whileÂ  the effect of rupiah exchange rate is positive insignificant toward the company value.The last summary of this research is recommended as an input for the investors that 4 variables that investigated in this research do not affect the company value significantly. This research has restrictiveness, they are the period of collecting sample is relatively short; there are no considerations among variables, and the internal factors of company presented in the financial report. Keyword : Inflation, Dividend Policy, Leverage, Rupiah Exchange Rate, Interest Rate And Company Value